Intraocular amphiregulin and axial elongation in non-human adolescent primates - Dong, Li; Wu, Hao Tian; Zhang, Rui Heng; Niu, Ling Han; Wang, Ya Xing; Wei, Wen Bin; Panda-Jonas, Songhomitra; Jonas, Jost B. (Experimental eye research, 2024)
The purpose of the experimental interventional study was to examine the influence of intraocularly applied amphiregulin, a member of the epidermal growth factor (EGF) family, on axial length in young non-human primates. It included three non-human primates (Macaca mulatta), aged 4-6 years. The left eyes received three intravitreal injections of amphiregulin (400ng/50 μl) in intervals of 4 weeks, while the right eyes received three intravitreal injections of phosphate buffered solution (50 μl) at the same time points. Ocular biometry was performed in weekly intervals. At baseline, the left eyes (study eyes) were shorter than the right (control) eyes (20.69 ± 0.21 mm versus 20.79 ± 0.24 mm; P < 0.001), with an inter-eye axial length (AL) difference (left minus right eye) of −0.10 ± 0.23 mm. Inter-eye AL difference increased (P < 0.001) to 0.15 ± 0.18 mm at study end, at 12 weeks after baseline. Axial elongation during the study was higher (P < 0.001) in the left eyes (20.69 ± 0.21 mm to 21.05 ± 0.29 mm or 0.36 ± 0.30 mm) than in the right eyes (20.79 ± 0.24 mm to 20.90 ± 0.31 mm or 0.11 ± 0.17 mm). In a parallel manner, inter-eye difference in vitreous cavity depth combined with lens thickness (left eye minus right eye) increased from −0.04 ± 0.17 mm at baseline to −0.02 ± 0.21 mm (P = 0.02), 0.04 ± 0.10 mm (P = 0.002), and to 0.42 ± 0.67 mm (P < 0.001) at 5, 6, and 12 weeks after baseline, respectively. The results suggest that intravitreally applied amphiregulin as EGF family member led to an increase in axial length in adolescent non-human primates. It supports the hypothesis of amphiregulin as EGF family member being involved in the process of axial elongation.